2018
DOI: 10.3389/fpubh.2018.00306
|View full text |Cite
|
Sign up to set email alerts
|

A New High Hydrostatic Pressure Process to Assure the Microbial Safety of Human Milk While Preserving the Biological Activity of Its Main Components

Abstract: Background: The main process used to pasteurize human milk is the low-temperature, long-time Holder method. More recently, the high-temperature, short-time method has been investigated. Both processes lead to the appropriate inactivation of vegetative bacterial forms but are ineffective against bacterial spores.Research Aims/Questions: We aimed to accomplish two main objectives: inactivation of all pathogens, including spores; and preservation of the activity of milk components.Design/Methods: Recently, a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 52 publications
(45 reference statements)
7
72
1
Order By: Relevance
“…Under these conditions, the activity of certain important human milk biological components, such as lipase activity and immune proteins, is maintained. These results were obtained with a pressure of 350 MPa (40).…”
Section: State Of the Art And Future Trendsmentioning
confidence: 77%
“…Under these conditions, the activity of certain important human milk biological components, such as lipase activity and immune proteins, is maintained. These results were obtained with a pressure of 350 MPa (40).…”
Section: State Of the Art And Future Trendsmentioning
confidence: 77%
“…HPP was shown to be even more effective in comparison to holder pasteurization in the elimination of inoculated microbiological flora (total viable count microorganisms, S. aureus ) of raw milk [12]. A recent study showed that high pressure processing can be an effective method of eliminating bacteria which produce spores, like Bacillus cereus [13]. Foods pasteurized by means of the HPP method are freer of microbes than products of thermal processing.…”
Section: Resultsmentioning
confidence: 99%
“…The HPP conditions used in our study (550 MPa, 5 min) best preserved BSSL activity compared with IR, UV-C, and LTLT. Moreover, HPP has been previously shown to improve the retention of other bioactive milk proteins such as lactoferrin, lysozyme and immunological components compared with LTLT (6,9,14). Additionally, HPP minimized changes in the free fatty acid content and oxidative stability of human milk compared to Holder pasteurization (7).…”
Section: Discussionmentioning
confidence: 99%
“…Non-profit milk banks pasteurize [heating at 62.5 • C for 30 min, also known as low-temperature long-time pasteurization (LTLT)] donor milk to inactivate bacteria and viruses. However, BSSL is completely degraded by Holder pasteurization (5)(6)(7). The degradation of BSSL by pasteurization further reduces overall fat absorption from human milk 17-30%, decreasing weight gain and linear growth of preterm infants over time (1,5,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation